In vitro cytotoxic and inhibitory effect of tramadol, flunitrazepam and levonogestrel on neutrophils and myeloperoxidase - Bukoye Oyewo, Emmanuel; Oluwafunmilayo Ajayi, Juliana; Joseph Oso, Babatunde; Sanmi Adekunle, Adeniran; Temidayo Ige, Peace; Ayomide Akomolafe, Peter (Trends in Immunotherapy, 2024)
The abuse of flunitrazepam, tramadol and levonorgestrel among adolescents is a major problem, with adverse effects on the immune system. Neutrophils serve as the host primary defense and employ the role of an essential enzyme, myeloperoxidase. This study investigated the in vitro effect of flunitrazepam, tramadol and levonorgestrel on the activity of the neutrophil. Neutrophils were isolated from blood samples of volunteers and seeded in culture plates, and then treated with flunitrazepam, tramadol and levonorgestrel. Trypan blue exclusion assay was used to assess the cytotoxic effect of flunitrazepam, (15, 150, 1500, 15,000, 150,000 ng/mL), tramadol (300, 3000, 30,000 µg/ml) and levonorgestrel (18.5, 185 and 1850 ng/mL) on the neutrophils, and the effect flunitrazepam (150,000 ng/mL), tramadol (30,000 µg/ml) and levonorgestrel (1850 ng/mL) on myeloperoxidase activity was assessed. The viability of neutrophils treated with flunitrazepam, (15,000, 150,000 ng/mL), tramadol (300, 3000, 30,000 µg/ml) and levonorgestrel (18.5, 185 and 1850 ng/mL) decreased significantly (p < 0.05) compared with control. Myeloperoxidase activity in neutrophils treated with flunitrazepam (150,000 ng/mL), tramadol (30,000 µg/ml) and levonorgestrel (1850 ng/mL) decreased significantly (p < 0.05) compared with background and positive control. This study revealed that flunitrazepam, tramadol and levonorgestrel altered the activity of myeloperoxidase and phagocytic activities of the neutrophil.